Principles of Interaction between Historic and Contemporary Architecture during the Modernization of Museums: Strategies of the 20th–21st Centuries - Fedotova, Natalia Iu. (Actual Problems of Theory and History of Art, 2016)
The article analyzes the key principles of interaction between various architectural style trends during modernization of museum complexes. The first (“nuance”) principle represents the consonance of various architectural styles that do not break the uniformity of an architectural image of the museum. This principle of modernization does not mean a duplication of the historic building; it is about using the same stylistic frame. The second (“contrasting”) principle is the most outstanding one because it represents the artistic spirit of contemporaneity. Architecture of a new building or museum site represents the style contrastively juxtaposed to historic premises. The modernization principles are reviewed using examples of international experience (Prado National Museum and Reina Sofia National Art Center). The author analyzes the spaceplanning, design, and technical solutions of museum facilities, their functional value and artistic character.
Keywords: museum; architecture; modernization; refurbishing; Prado National Museum; Reina Sofia National Art Center